Prvoletna črnoglavka Sylvia atricapilla ujeta v Rusiji med jesensko selitvijo v smeri SSV - Černecov, Nikita (Acrocephalus, 1998)
On October 13th and 19th 1995, a first-year female Blackcap ringed on September 25th 1995 in Maribor, Slovenia, was caught in Rybachy, Kaliningrad region, Russia. The distance between the two places was 1027 km, direction 20 NNE. The author of the article believes that such unusual migratory route by the Blackcap could not be attributed to the so-called juvenile dispersal, as it was simply too late in the season and the distance was too long as well. As a possible explanation for this phenomenon he suggests changes in the genetically determined migratory direction noticed already in a part of Central European Blackcaps, which have lately been overwintering in the British Isles,...
Keywords: birds; Košir, Martin; ornithology; ornitologija; ptiči